The proton-[omega] correlation function in Au+Au collisions at √sNN=200 GeV - Adam, Jaroslav; Deppner, Ingo Martin; Herrmann, Norbert (Physics letters, 2019)
We present the first measurement of the proton-Ω correlation function in heavy-ion collisions for the central (0-40%) and peripheral (40-80%) Au+Au collisions at sNN=200 GeV by the STAR experiment at the Relativistic Heavy-Ion Collider (RHIC). Predictions for the ratio of peripheral collisions to central collisions for the proton-Ω correlation function are sensitive to the presence of a nucleon-Ω bound state. These predictions are based on the proton-Ω interaction extracted from (2+1)-flavor lattice QCD calculations at the physical point. The measured ratio of the proton-Ω correlation function between the peripheral (small system) and central (large system) collisions is less than unity for relative momentum smaller than 40 MeV/c. Comparison of our measured correlation ratio with theoretical calculation slightly favors a proton-Ω bound system with a binding energy of ∼ 27 MeV.